Fathers of Young Deaf or Hard-of-Hearing Children: A Systematic Review. (18th January 2021) - Szarkowski, Amy; Dirks, Evelien
Abstract: Much of the literature exploring the role of parents of children who are deaf or hard of hearing (DHH) has focused on mothers; yet, the involvement and perspectives of fathers is valuable and warrants attention. Following the PRISMA guidelines, this systematic literature review examined the peer-reviewed research that has differentially explored the experiences of fathers and mothers of young DHH children. Utilizing three databases (Web of Science, PsychINFO, Scopus) and spanning 50 years (1969–2019), 457 non-duplicated articles were identified that included the fathers of DHH children, birth to six years. Independent review of the titles, abstracts, and keywords by the authors limited these to 119. Full manuscripts were assessed for eligibility; 37 were deemed appropriate for inclusion in this systematic review. The papers included have been organized into the following themes: perspectives on parenting, parental stress and coping, parent-child interaction, involvement in early intervention, parental self-efficacy, and benefits of fathers' inclusion. Recommendations for future research include: (a) actively recruiting fathers in research, (b) differentially analyzing fathers' and mothers' experiences in research studies, (c) using information gleaned from research regarding father-child and mother-child interactions to guide interventions/programming, (d) recognizing the bidirectional influences of fathers and their DHH children, (e) moving beyond descriptive studies to explore fathers' influences on child outcomes, and (f) recognizing diverse family constellations.